On Piano Playing. Motion, Sound and Expression - Sandor, Gyorgy (Belmont Schirmer, 1995)
On Piano Playing is Gyorgy Sandor's complete, practical program for developing the physical skills essential to accomplished playing.
Keywords: Piano; Method